SISTEMA DE ELETROCARDIOGRAFIA DE BAIXO CUSTO BASEADO EM PLATAFORMAS MÓVEIS PARA APLICAÇÃO EM TELEMEDICINA - Robson, Ricardo Rodrigues (2007)
The majority of cardiovascular diseases cases occur in low and middle income countries. Even at high-income countries, heart diseases demands great economic resources. Thus, this work proposes a low-cost telemedicine application to collect, transmit and display ECG exams for cardiologists. To reduce the final cost, the system proposed here employs a data acquisition board based on low-cost microcontroller, low-cost PDA equipment with infrared interface and open source software. Costing 76% less than the revised commercial and academic equipments, the proposed system achieves or even surpasses their performance in resolution and signal quality.